11-Hydroxyeicosatetraenoics induces cellular hypertrophy in an enantioselective manner - Helal, Sara A.; El-Sherbeni, Ahmed A.; El-Kadi, Ayman O. S. (Frontiers in Pharmacology, 2024)
Background R/S enantiomers of 11-hydroxyeicosatertraenoic acid (11-HETE) are formed from arachidonic acid by enzymatic and non-enzymatic pathways. 11-HETE is predominately formed by the cytochrome P450 1B1 (CYP1B1). The role of CYP1B1 in the development of cardiovascular diseases is well established. Objectives This study aimed to assess the cellular hypertrophic effect of 11-HETE enantiomers in human RL-14 cardiomyocyte cell line and to examine their association with CYP1B1 levels. Methods Human fetal ventricular cardiomyocyte, RL-14 cells, were treated with 20 µM (R) or (S) 11-HETE for 24 h. Thereafter, cellular hypertrophic markers and cell size were then determined using real-time polymerase chain reaction (RT-PCR) and phase-contrast imaging, respectively. The mRNA and protein levels of selected CYPs were determined using RT-PCR and Western blot, respectively. In addition, we examined the effect of (R) and (S) 11-HETE on CYP1B1 catalytic activity using human recombinant CYP1B1 and human liver microsomes. Results Both (R) and (S) 11-HETE induced cellular hypertrophic markers and cell surface area in RL-14 cells. Both enantiomers significantly upregulated CYP1B1, CYP1A1, CYP4F2, and CYP4A11 at the mRNA and protein levels, however, the effect of the S-enantiomer was more pronounced. Furthermore, 11(S)-HETE increased the mRNA and protein levels of CYP2J and CYP4F2, whereas 11(R)-HETE increased only CYP4F2. Only 11(S)-HETE significantly increased the catalytic activity of CYP1B1 in recombinant human CYP1B1, suggesting allosteric activation in an enantioselective manner. Conclusion Our study provides the first evidence that 11-HETE can induce cellular hypertrophy in RL-14 cells via the increase in CYP1B1 mRNA, protein, and activity levels.